Activation of the Epidermal Growth Factor Receptor Signal Transduction Pathway Stimulates Tyrosine Phosphorylation of Protein Kinase C δ - Mitchell F. Denning; Andrzej A. Dlugosz; David W. Threadgill; Terry Magnuson; Stuart H. Yuspa (1996)
The expression of an oncogenic rasHa gene in epidermal keratinocytes stimulates the tyrosine phosphorylation of protein kinase C δ and inhibits its enzymatic activity (Denning, M. F., Dlugosz, A. A., Howett, M. K., and Yuspa, S. H.(1993) J. Biol. Chem. 268, 26079-26081). Keratinocytes expressing an activated rasHa gene secrete transforming growth factor α (TGFα) and have an altered response to differentiation signals involving protein kinase C (PKC). Because the neoplastic phenotype of v-rasHa expressing keratinocytes can be partially mimicked in vitro by chronic treatment with TGFα and the G protein activator aluminum fluoride (AlF-4), we determined if TGFα or AlF-4 could induce tyrosine phosphorylation of PKCδ. Treatment of primary keratinocyte cultures for 4 days with TGFα induced tyrosine phosphorylation of PKCδ, whereas AlF-4 only slightly stimulated PKCδ tyrosine phosphorylation. The PKCδ that was tyrosine-phosphorylated in response to TGFα had reduced activity compared with the nontyrosine-phosphorylated PKCδ. Treatment of keratinocytes expressing a normal epidermal growth factor receptor (EGFR) with TGFα or epidermal growth factor for 5 min induced PKCδ tyrosine phosphorylation. This acute epidermal growth factor treatment did not induce tyrosine phosphorylation of PKCδ in keratinocytes isolated from waved-2 mice that have a defective epidermal growth factor receptor. In addition, the level of PKCδ tyrosine phosphorylation in v-rasHa-transduced keratinocytes from EGFR null mice was substantially lower than in v-rasHa transduced wild type cells, suggesting that activation of the EGFR is important for PKCδ tyrosine phosphorylation in ras transformation. However, purified EGFR did not phosphorylate recombinant PKCδ in vitro, whereas members of the Src family (c-Src, c-Fyn) and membrane preparations from keratinocytes did. Furthermore, clearing c-Src or c-Fyn from keratinocyte membrane lysates decreased PKCδ tyrosine phosphorylation, and c-Src and c-Fyn isolated from keratinocytes treated with TGFα had increased kinase activity. Acute or chronic treatment with TGFα did not induce significant PKCδ translocation in contrast to the phorbol ester 12-O-tetradecanoylphorbol-13-acetate, which induced both translocation and tyrosine phosphorylation of PKCδ. This suggests that TGFα-induced tyrosine phosphorylation of PKCδ results from the activation of a tyrosine kinase rather than physical association of PKCδ with a membrane-anchored tyrosine kinase. Taken together, these results indicate that PKCδ activity is inhibited by tyrosine phosphorylation in response to EGFR-mediated signaling and activation of a member of the Src kinase family may be the proximal tyrosine kinase acting on PKCδ in keratinocytes. The expression of an oncogenic rasHa gene in epidermal keratinocytes stimulates the tyrosine phosphorylation of protein kinase C δ and inhibits its enzymatic activity (Denning, M. F., Dlugosz, A. A., Howett, M. K., and Yuspa, S. H.(1993) J. Biol. Chem. 268, 26079-26081). Keratinocytes expressing an activated rasHa gene secrete transforming growth factor α (TGFα) and have an altered response to differentiation signals involving protein kinase C (PKC). Because the neoplastic phenotype of v-rasHa expressing keratinocytes can be partially mimicked in vitro by chronic treatment with TGFα and the G protein activator aluminum fluoride (AlF-4), we determined if TGFα or AlF-4 could induce tyrosine phosphorylation of PKCδ. Treatment of primary keratinocyte cultures for 4 days with TGFα induced tyrosine phosphorylation of PKCδ, whereas AlF-4 only slightly stimulated PKCδ tyrosine phosphorylation. The PKCδ that was tyrosine-phosphorylated in response to TGFα had reduced activity compared with the nontyrosine-phosphorylated PKCδ. Treatment of keratinocytes expressing a normal epidermal growth factor receptor (EGFR) with TGFα or epidermal growth factor for 5 min induced PKCδ tyrosine phosphorylation. This acute epidermal growth factor treatment did not induce tyrosine phosphorylation of PKCδ in keratinocytes isolated from waved-2 mice that have a defective epidermal growth factor receptor. In addition, the level of PKCδ tyrosine phosphorylation in v-rasHa-transduced keratinocytes from EGFR null mice was substantially lower than in v-rasHa transduced wild type cells, suggesting that activation of the EGFR is important for PKCδ tyrosine phosphorylation in ras transformation. However, purified EGFR did not phosphorylate recombinant PKCδ in vitro, whereas members of the Src family (c-Src, c-Fyn) and membrane preparations from keratinocytes did. Furthermore, clearing c-Src or c-Fyn from keratinocyte membrane lysates decreased PKCδ tyrosine phosphorylation, and c-Src and c-Fyn isolated from keratinocytes treated with TGFα had increased kinase activity. Acute or chronic treatment with TGFα did not induce significant PKCδ translocation in contrast to the phorbol ester 12-O-tetradecanoylphorbol-13-acetate, which induced both translocation and tyrosine phosphorylation of PKCδ. This suggests that TGFα-induced tyrosine phosphorylation of PKCδ results from the activation of a tyrosine kinase rather than physical association of PKCδ with a membrane-anchored tyrosine kinase. Taken together, these results indicate that PKCδ activity is inhibited by tyrosine phosphorylation in response to EGFR-mediated signaling and activation of a member of the Src kinase family may be the proximal tyrosine kinase acting on PKCδ in keratinocytes. INTRODUCTIONThe protein kinase C (PKC) ( 1The abbreviations used are: PKCprotein kinase CEGFepidermal growth factorPDGFplatelet-derived growth factorTPA12-O-tetradecanoylphorbol-13-acetateEGFREGF receptorTGFtransforming growth factor.) family of serine/threonine protein kinases is a central component of phospholipase-coupled growth factor receptor signaling pathways(1.Stabel S. Parker P.J. Pharmacol. & Ther. 1991; 51: 71-95Crossref PubMed Scopus (452) Google Scholar). The enzymatic activities of several PKC isoforms are regulated by the allosteric activators diacylglycerol and Ca2+, which are elevated in response to growth factor receptor activation(2.Nishizuka Y. Science. 1992; 258: 607-614Crossref PubMed Scopus (4215) Google Scholar). The G protein Ras is also a component of the mitogen-activated protein kinase signaling pathways for growth factors such as epidermal growth factor (EGF) and platelet derived growth factor (PDGF). In addition, PKCα can directly affect the mitogen-activated protein kinase pathway by phosphorylating and stimulating the autokinase activity of Raf-1(3.Kolch W. Heidecker G. Kochs G. Hummel R. Vahidi H. Mischak H. Finkenzeller G. Marme D. Rapp U.R. Nature. 1993; 364: 249-252Crossref PubMed Scopus (1152) Google Scholar). Ras can act either as a regulator or effector of PKC function, but the molecular mechanisms involved are unclear(4.Lacal J.C. Fleming T.P. Warren B.S. Blumberg P.M. Aaronson S.A. Mol. Cell. Biol. 1987; 7: 4146-4149Crossref PubMed Scopus (76) Google Scholar, 5.Denning M.F. Dlugosz A.A. Howett M.K. Yuspa S.H. J. Biol. Chem. 1993; 268: 26079-26081Abstract Full Text PDF PubMed Google Scholar, 6.Haliotis T. Trimble W. Chow S. Bull S. Mills G. Girard P. Kuo J.F. Hozumi N. Int. J. Cancer. 1990; 45: 1177-1183Crossref PubMed Scopus (26) Google Scholar, 7.Lacal J.C. Cuadrado A. Jones J.E. Trotta R. Burstein D.E. Thomson T. Pellicer A. Mol. Cell. Biol. 1990; 10: 2983-2990Crossref PubMed Scopus (24) Google Scholar, 8.Vaidya T.B. Weyman C.M. Teegarden D. Ashendel C.L. Taparowsky E.J. J. Cell Biol. 1991; 114: 809-820Crossref PubMed Scopus (43) Google Scholar).In epidermal keratinocytes, Ras can have both positive and negative effects on PKC signaling. Neoplastic mouse keratinocytes expressing an activated rasHa allele have increases in phosphatidylinositol turnover, diacylglycerol levels, and calcium-dependent PKC activity(9.Lee E. Punnonen K. Cheng C. Glick A. Dlugosz A. Yuspa S.H. Carcinogenesis. 1992; 13: 2367-2373Crossref PubMed Scopus (18) Google Scholar, 10.Dlugosz A.A. Cheng C. Williams E.K. Dharia A.G. Denning M.F. Yuspa S.H. Cancer Res. 1994; 54: 6413-6420PubMed Google Scholar). Activation of PKCα, the only calcium-dependent PKC isoform expressed in keratinocytes, is correlated with the expression of granular layer differentiation markers in normal keratinocytes and in v-rasHa expressing keratinocytes, where granular layer differentiation markers are up-regulated(10.Dlugosz A.A. Cheng C. Williams E.K. Dharia A.G. Denning M.F. Yuspa S.H. Cancer Res. 1994; 54: 6413-6420PubMed Google Scholar, 11.Denning M.F. Dlugosz A.A. Williams E.K. Szallasi Z. Blumberg P.M. Yuspa S.H. Cell Growth & Differ. 1995; 6: 149-157PubMed Google Scholar). Keratinocytes expressing a v-rasHa oncogene also have decreased Ca2+-independent PKC activity and have a block in their ability to commit to Ca2+ and TPA-induced terminal differentiation(10.Dlugosz A.A. Cheng C. Williams E.K. Dharia A.G. Denning M.F. Yuspa S.H. Cancer Res. 1994; 54: 6413-6420PubMed Google Scholar, 12.Cheng C. Kilkenny A.E. Roop D. Yuspa S.H. Mol. Carcinogen. 1990; 3: 363-373Crossref PubMed Scopus (61) Google Scholar, 13.Diaz-Guerra M. Haddow S. Bauluz C. Jorcano J.L. Cano A. Balmain A. Quintanilla M. Cancer Res. 1992; 52: 680-687PubMed Google Scholar, 14.Yuspa S.H. Kilkenny A.E. Stanley J. Lichti U. Nature. 1985; 314: 459-462Crossref PubMed Scopus (88) Google Scholar). The block in differentiation response may be due to the tyrosine phosphorylation and inactivation of PKCδ because the kinase inhibitor staurosporine blocks PKCδ tyrosine phosphorylation and induces terminal differentiation of neoplastic keratinocytes(5.Denning M.F. Dlugosz A.A. Howett M.K. Yuspa S.H. J. Biol. Chem. 1993; 268: 26079-26081Abstract Full Text PDF PubMed Google Scholar). In addition, v-rasHa transformation of keratinocytes up-regulates epidermal growth factor receptor (EGFR) ligand expression and induces the secretion of transforming growth factor α (TGFα)(15.Dlugosz A.A. Cheng C. Williams E.K. Darwiche N. Dempsey P.J. Mann B. Dunn A.R. Coffey Jr., R.J. Yuspa S.H. Cancer Res. 1995; 55: 1883-1893PubMed Google Scholar, 16.Glick A.B. Sporn M.B. Yuspa S.H. Mol. Carcinogen. 1991; 4: 210-219Crossref PubMed Scopus (83) Google Scholar, 17.Cheng C. Tennenbaum T. Dempsey P.J. Coffey R.J. Yuspa S.H. Dlugosz A.A. Cell Growth & Differ. 1993; 4: 317-327PubMed Google Scholar). Several studies have indicated that increased secretion of TGFα can substitute for rasHa mutations in the altered response to differentiation signals (17.Cheng C. Tennenbaum T. Dempsey P.J. Coffey R.J. Yuspa S.H. Dlugosz A.A. Cell Growth & Differ. 1993; 4: 317-327PubMed Google Scholar) and can initiate skin carcinogenesis(18.Vassar R. Hutton M.E. Fuchs E. Mol. Cell. Biol. 1992; 12: 4643-4653Crossref PubMed Scopus (101) Google Scholar, 19.Wang X.J. Greenhalgh D.A. Eckhardt J.N. Rothnagel J.A. Roop D.R. Mol. Carcinogen. 1994; 10: 15-22Crossref PubMed Scopus (52) Google Scholar).In this study, we further characterized the signal transduction pathways regulating PKCδ tyrosine phosphorylation in murine keratinocytes. We demonstrate that TGFα is able to induce tyrosine phosphorylation of PKCδ resulting in inhibition of its activity. Although tyrosine phosphorylation of PKCδ in intact cells requires a functional EGFR, it is not directly mediated by EGFR and may involve a member of the Src kinase family. Tyrosine phosphorylation of PKCδ by the EGFR pathway demonstrates a perturbation of PKC signaling by TGFα that may contribute to the process of neoplastic transformation in epithelial cells.EXPERIMENTAL PROCEDURESMaterialsPurified EGFR was from Promega, and Src and Fyn kinases were purchased from Upstate Biotechnology Inc. PKC isozymes were produced in SF9 insect cells using a baculovirus expression system as described previously (20.Kazanietz M.G. Areces L.B. Bahador A. Mischak H. Goodnight J. Mushinski J.F. Blumberg P.M. Mol. Pharmacol. 1993; 44: 298-307PubMed Google Scholar) and were kindly provided by Drs. Marcelo G. Kazanietz and Peter M. Blumberg of the Laboratory of Cellular Carcinogenesis and Tumor Promotion at the National Cancer Institute.Cell CulturePrimary keratinocytes were isolated from newborn BALB/c, waved-2 mice, and EGFR +/+ or -/- newborn mice(21.Threadgill D.W. Dlugosz A.A. Hansen L.A. Tennenbaum T. Lichti U. Yee D. LaMantia C. Mourton T. Herrup K. Harris R.C. Barnard J.A. Yuspa S.H. Coffey R.J. Magnuson T. Science. 1995; 269: 230-234Crossref PubMed Scopus (1257) Google Scholar). The waved-2 mice were obtained from Jackson Laboratories. The phenotype of the wa-2/wa-2 mice were distinguished from the +/+ and +/wa-2 mice by the curly whiskers observed in the wa-2/wa-2 newborn mice (22.Luetteke N.C. Phillips H.K. Qiu T.H. Copeland N.G. Earp H.S. Jenkins N.A. Lee D.C. Genes & Dev. 1994; 8: 399-413Crossref PubMed Scopus (389) Google Scholar). The keratinocytes were cultured in Eagle's minimal essential medium containing 8% Chelex-treated (Bio-Rad) fetal bovine serum with the final Ca2+ concentration adjusted to 0.05 mM as described(23.Hennings H. Michael D. Cheng C. Steinert P. Holbrook K. Yuspa S.H. Cell. 1980; 19: 245-254Abstract Full Text PDF PubMed Scopus (1494) Google Scholar). The EGFR genotype of newborn mice was determined by polymerase chain reaction amplification of tail DNA as described previously(21.Threadgill D.W. Dlugosz A.A. Hansen L.A. Tennenbaum T. Lichti U. Yee D. LaMantia C. Mourton T. Herrup K. Harris R.C. Barnard J.A. Yuspa S.H. Coffey R.J. Magnuson T. Science. 1995; 269: 230-234Crossref PubMed Scopus (1257) Google Scholar). Primary keratinocytes from the EGFR +/+ and -/- mice (21.Threadgill D.W. Dlugosz A.A. Hansen L.A. Tennenbaum T. Lichti U. Yee D. LaMantia C. Mourton T. Herrup K. Harris R.C. Barnard J.A. Yuspa S.H. Coffey R.J. Magnuson T. Science. 1995; 269: 230-234Crossref PubMed Scopus (1257) Google Scholar) were cultured in 0.05 mM Ca2+-containing medium with 1 ng/ml keratinocyte growth factor for 2-3 days to stimulate proliferation of the EGFR -/- keratinocytes. After reaching approximately 80% confluence, the cells were cultured without keratinocyte growth factor for 3-4 days before harvesting. For the introduction of a v-rasHa gene into cells, keratinocytes were exposed to 4 μg/ml polybrene in the absence or the presence of a replication-defective retrovirus containing the v-rasHa gene and cultured 4-6 days before use(24.Roop D.R. Lowy D.R. Tambourin P.E. Strickland J. Harper J.R. Balaschak M. Spangler E.F. Yuspa S.H. Nature. 1986; 323: 822-824Crossref PubMed Scopus (208) Google Scholar).Immunoblotting and ImmunoprecipitationsFor the extraction of proteins, the cells were washed twice in cold phosphate-buffered saline, scraped into immunoprecipitation lysis buffer (50 mM HEPES, pH 7.5, 150 mM NaCl, 10% glycerol, 1% Triton X-100, 1.5 mM EGTA, 1 mM NaVO3, 10 μM NaF, 1 mM phenylmethylsulfonyl fluoride, 10 μg/ml aprotinin, and 10 μg/ml leupeptin), and separated by SDS-polyacrylamide gel electrophoresis. Proteins were transferred to nitrocellulose electrophoretically, blocked with 5% nonfat dry milk, and stained with the indicated primary antibodies as described previously(5.Denning M.F. Dlugosz A.A. Howett M.K. Yuspa S.H. J. Biol. Chem. 1993; 268: 26079-26081Abstract Full Text PDF PubMed Google Scholar, 11.Denning M.F. Dlugosz A.A. Williams E.K. Szallasi Z. Blumberg P.M. Yuspa S.H. Cell Growth & Differ. 1995; 6: 149-157PubMed Google Scholar). The immunoblots were incubated with antibodies specific for PKCδ at a 1:500 dilution (Calbiochem) or phosphotyrosine at 1 μg/ml (clone 4G10, Upstate Biotechnology Inc.). Immunoblotted proteins were detected using the Renaissance Chemiluminescence Reagents (DuPont NEN) with horseradish peroxidase-conjugated secondary antibodies (Bio-Rad) at 1:5000 dilution. The immunoblots were quantitated using a Molecular Dynamics Personal Densitometer.Immunoprecipitations were performed as described previously(5.Denning M.F. Dlugosz A.A. Howett M.K. Yuspa S.H. J. Biol. Chem. 1993; 268: 26079-26081Abstract Full Text PDF PubMed Google Scholar). Briefly, the cells were washed with phosphate-buffered saline and scraped into immunoprecipitation lysis buffer, and equal amounts of protein were immunoprecipitated with 20 μl of protein A/G PLUS-Agarose (Santa Cruz Biotechnology) and either 2.5 μg anti-phosphotyrosine antibody or 0.5-1 μl of anti-PKCδ antibody. The c-Src and c-Fyn immunoprecipitations were performed with 2 μg of antibody from Santa Cruz Biotechnology, Inc. (sc-19 and sc-16 respectively) and 50 μl protein A-Sepharose from Sigma. For some phosphotyrosine immunoprecipitations, an agarose-conjugated anti-phosphotyrosine monoclonal antibody from Upstate Biotechnology Inc. was used. For immunoblotting, the immunoprecipitates were washed three times with RIPA buffer (50 mM Tris-HCl, pH 8.0, 150 mM NaCl, 1% Triton X-100, 0.1% SDS, and 1% sodium deoxycholate) and boiled in 20 μl of SDS sample buffer(25.Laemmli U.K. Nature. 1970; 227: 680-685Crossref PubMed Scopus (206048) Google Scholar).In Vitro Kinase AssaysTyrosine kinase reactions were performed in a volume of 20-30 μl containing 50 mM Tris, pH 7.5, 10 mM MgCl2, 2 mM MnCl2, 100 μM phenylmethylsulfonyl fluoride, 100 μM NaVO3, and 1 mM NaF. PKC isozymes from baculovirus-infected Sf-9 cells were included as substrates for either Src or Fyn kinase (10 units) or keratinocyte membranes (25 μg of protein). The keratinocyte membranes were prepared from normal primary keratinocytes by scraping the cells into hypotonic lysis buffer (1 mM HEPES, pH 7.5, 5 mM MgCl2, and 100 μM phenylmethylsulfonyl fluoride) and spinning at approximately 50 × g for 5 min at 4°C. The supernatant was then spun in a microcentrifuge for 20 min, and the membrane pellet resuspended in assay buffer and used as a source of tyrosine kinase. The reactions were started by adding 25 μM ATP and incubated for 10 min at 30°C. Tyrosine phosphorylation was assessed by immunoblotting with an anti-phosphotyrosine antibody. For the Src and Fyn immunoprecipitation kinase assays, the immunoprecipitates were washed twice with immunoprecipitation lysis buffer, twice with assay buffer (20 mM HEPES, pH 7.4, 3 mM MnCl2, and 5 mM MgCl2), and incubated in 30 μl of assay buffer containing 10 μM ATP for 10 min at 30°C. The Sepharose beads were washed once in immunoprecipitation lysis buffer and analyzed by immunoblotting with an anti-phosphotyrosine antibody.PKC assays of tyrosine-phosphorylated and nontyrosine-phosphorylated PKCδ were performed as described previously with minor modifications (5.Denning M.F. Dlugosz A.A. Howett M.K. Yuspa S.H. J. Biol. Chem. 1993; 268: 26079-26081Abstract Full Text PDF PubMed Google Scholar). Primary keratinocytes were cultured in 10 ng/ml TGFα for 4 days to induce the tyrosine phosphorylation of a fraction (~50%) of PKCδ. Lysates were prepared (n = 3) and immunoprecipitated with an anti-phosphotyrosine antibody for 2.5 h. The phosphotyrosine-cleared lysates were taken for immunoprecipitation of nontyrosine-phosphorylated PKCδ. Both phosphorylated and nonphosphorylated samples were immunoprecipitated for PKCδ overnight in the presence of 30 mMp-nitrophenylphosphate to release phosphotyrosine containing proteins from the anti-phosphotyrosine antibody. The immunoprecipitates were washed once with immunoprecipitation lysis buffer and twice in 50 mM Tris-HCl, pH 7.4, and resuspended in 25 μl of Tris-HCl and 5 mM 2-mercaptoethanol. PKC assays were performed on the immunoprecipitated PKCδ in the presence or the absence of 1 μM TPA as described by Nakadate et al.(26.Nakadate T. Jeng A.Y. Blumberg P.M. Biochem. Pharmacol. 1988; 37: 1541-1545Crossref PubMed Scopus (161) Google Scholar) except that the PKC substrate peptide [ser25] (Life Technologies, Inc.) was the phosphate acceptor, and 20%/80% phosphatidylserine/phosphatidylcholine vesicles were the phospholipid. After the enzyme reaction, the agarose beads were spun, and 30 μl of supernatant was spotted for scintillation counting. The PKCδ remaining on the beads was boiled in SDS sample buffer and analyzed by anti-PKCδ immunoblot to correct for differences in the amount of PKCδ in the assay.RESULTSTGFα Induces Tyrosine Phosphorylation of PKCδ in Normal KeratinocytesBecause treatment of primary keratinocyte cultures with TGFα and the nonspecific G protein activator AlF-4 elicits many phenotypic changes characteristic of v-rasHa transformation(9.Lee E. Punnonen K. Cheng C. Glick A. Dlugosz A. Yuspa S.H. Carcinogenesis. 1992; 13: 2367-2373Crossref PubMed Scopus (18) Google Scholar), we examined whether the tyrosine phosphorylation of PKCδ was also induced by these pharmacological agents. Culturing primary keratinocytes in the presence of 10 ng/ml TGFα for 4 days induced tyrosine phosphorylation of PKCδ (27-fold), whereas a 4-day AlF-4 (1 μM AlCl3 and 1 mM NaF) treatment induced tyrosine phosphorylation only slightly (Fig. 1A). The combined treatment of TGFα and AlF-4 resulted in a more than additive increase in PKCδ tyrosine phosphorylation (48-fold).Because TGFα was a more effective inducer of PKCδ tyrosine phosphorylation than AlF-4, we further analyzed TGFα-induced PKCδ tyrosine phosphorylation. The kinetics of TGFα-induced PKCδ tyrosine phosphorylation were biphasic (Fig. 1B). Tyrosine phosphorylation of PKCδ was increased approximately 8-fold after a 5-min TGFα treatment (10 ng/ml), returned toward basal levels by 1-2 h, and increased again from 4 and 6 h (9-11-fold), remaining elevated (4-fold) even after 24 h of TGFα treatment. The total levels of PKCδ did not change appreciably during this time. Acute and chronic treatment with EGF also induced PKCδ tyrosine phosphorylation (see Fig. 3A).Figure 3:Mutant alleles of the EGFR inhibit PKCδ tyrosine phosphorylation. A, primary keratinocytes were isolated from mice having a wild type EGFR (BALB/c, +/+ and +/wa-2) and from waved-2 mice homozygous for the mutant EGFR (wa-2/wa-2). The keratinocytes were cultured and infected with v-rasHa for 5 days (v-ras), treated with 10 ng/ml EGF for 4 days (EGF 4D), or 5 min (EGF 5 M), and PKCδ was immunoprecipitated from cellular lysates (750 μg of protein). The immunoprecipitates were immunoblotted with an anti-phosphotyrosine antibody (Anti p-Tyr) and anti-PKCδ antibody (Anti PKCδ). Similar results were obtained in two additional experiments. B, primary keratinocytes were isolated from mice having a wild type EGFR (+/+) and from EGFR null mice (-/-). The keratinocytes were initially cultured in 1 ng/ml keratinocyte growth factor for 3 days, switched to unsupplemented medium, and either treated with 100 nM TPA for 10 min (TPA) or infected with v-rasHa for 4 days (ras). Cellular lysates were immunoprecipitated with anti-phosphotyrosine antibody (p-Tyr IP), and gel separated total lysates (Total) were immunoblotted for the detection of total PKCδ levels with the anti-PKCδ antibody. A similar result was observed in one additional experiment.View Large Image Figure ViewerDownload Hi-res image Download (PPT)TGFα-induced Tyrosine Phosphorylation of PKCδ Inhibits Its ActivityThe tyrosine-phosphorylated form of PKCδ isolated from rasHa expressing keratinocytes is not activated by the phorbol ester TPA(5.Denning M.F. Dlugosz A.A. Howett M.K. Yuspa S.H. J. Biol. Chem. 1993; 268: 26079-26081Abstract Full Text PDF PubMed Google Scholar). To determine the effect of TGFα-induced tyrosine phosphorylation on PKCδ enzymatic activity, we performed assays on tyrosine-phosphorylated and nontyrosine-phosphorylated PKCδ isolated from keratinocytes treated for 4 days with 10 ng/ml TGFα (Fig. 2). Similar to the results for v-rasHa, the tyrosine-phosphorylated PKCδ from TGFα-treated cells had much lower constitutive activity, and TPA caused only a modest increase in activity. In fact, the specific activity of the tyrosine-phosphorylated PKCδ assayed in the presence of 1 μM TPA was substantially lower than the basal specific activity of the nontyrosine-phosphorylated PKCδ.Figure 2:Enzymatic activity of tyrosine-phosphorylated PKCδ. Primary keratinocytes were cultured for 4 days in medium containing 10 ng/ml TGFα, and the lysates (n = 3) were immunoprecipitated sequentially with an anti-phosphotyrosine antibody followed by an anti-PKCδ antibody. PKC activity was assayed in the tyrosine-phosphorylated and nonphosphorylated fractions in the presence or the absence of 1 μM TPA. For calculating PKCδ-specific activities, the amount of PKCδ in each assay tube was normalized by immunoblotting with an anti-PKCδ antibody. Similar results were obtained in two additional experiments.View Large Image Figure ViewerDownload Hi-res image Download (PPT)Tyrosine Phosphorylation of PKCδ Requires a Functional EGF ReceptorTo determine the contribution of the EGFR to PKCδ modification, keratinocytes were isolated from waved-2 mice that have a mutated EGFR with decreased tyrosine kinase activity(22.Luetteke N.C. Phillips H.K. Qiu T.H. Copeland N.G. Earp H.S. Jenkins N.A. Lee D.C. Genes & Dev. 1994; 8: 399-413Crossref PubMed Scopus (389) Google Scholar). Fig. 3A shows that tyrosine phosphorylation of PKCδ was induced by v-rasHa transduction and acute (5 min) or chronic (4 day) treatment with EGF in keratinocytes from BALB/c and phenotypically normal waved-2 mice (+/+ and +/wa-2). However, acute EGF treatment (5 min) did not induce tyrosine phosphorylation of PKCδ in the waved-2 keratinocytes (wa-2/wa-2), whereas chronic treatment or v-rasHa did. This is consistent with the defective but not inactive EGFR previously documented in the waved-2 strain(22.Luetteke N.C. Phillips H.K. Qiu T.H. Copeland N.G. Earp H.S. Jenkins N.A. Lee D.C. Genes & Dev. 1994; 8: 399-413Crossref PubMed Scopus (389) Google Scholar).Tyrosine phosphorylation of PKCδ was also assessed in keratinocytes isolated from mice harboring a disrupted EGFR gene(21.Threadgill D.W. Dlugosz A.A. Hansen L.A. Tennenbaum T. Lichti U. Yee D. LaMantia C. Mourton T. Herrup K. Harris R.C. Barnard J.A. Yuspa S.H. Coffey R.J. Magnuson T. Science. 1995; 269: 230-234Crossref PubMed Scopus (1257) Google Scholar). The immunoblots in Fig. 3B show that PKCδ was tyrosine-phosphorylated to a similar extent in both EGFR +/+ and -/- keratinocytes (1200 and 1700% increase, respectively) in response to acute TPA treatment. In contrast, v-rasHa transduction was less effective at inducing PKCδ tyrosine phosphorylation in the EGFR -/- keratinocytes than in the +/+ cells of the same genetic background (60 and 250% increase, respectively). There was no difference in the amount of total PKCδ between the EGFR +/+ and -/- keratinocytes. These genetic data strongly support the involvement of the EGFR in the v-rasHa-induced PKCδ tyrosine phosphorylation.In Vitro Tyrosine Phosphorylation of PKCδ by Src Family Kinases but Not EGFRThe ability of EGF or TGFα to rapidly induce the tyrosine phosphorylation of PKCδ suggests that the EGFR directly phosphorylates PKCδ. To test this hypothesis, we performed in vitro phosphorylation reactions using EGFR, c-Src, c-Fyn, or a membrane fraction from keratinocytes as the tyrosine kinase and recombinant PKCδ as the phosphate acceptor (Fig. 4A). As detected by phosphotyrosine immunoblotting, purified EGFR did not tyrosine phosphorylate PKCδ either in the total reaction mixture or in the PKCδ immunoprecipitate. The EGFR did autophosphorylate, indicating that it was enzymatically active. The tyrosine-phosphorylated band at the M2 of the EGFR in the PKCδ immunoprecipitates has never been detected in PKCδ immunoprecipitates from cell lysates and may associate with PKCδ only under these in vitro conditions. As shown in the PKCδ immunoprecipitate for c-Src and in the total blot for c-Fyn, both kinases were able to tyrosine phosphorylate PKCδ, consistent with previous work demonstrating the phosphorylation of PKCδ by c-Src and c-Fyn in vitro(27.Li W. Mischak H. Yu J.C. Wang L.M. Mushinski J.F. Heidaran M.A. Pierce J.H. J. Biol. Chem. 1994; 269: 2349-2352Abstract Full Text PDF PubMed Google Scholar, 28.Gschwendt M. Kielbassa K. Kittstein W. Marks F. FEBS Lett. 1994; 347: 85-89Crossref PubMed Scopus (98) Google Scholar). A crude membrane fraction from normal keratinocytes also mediated tyrosine phosphorylation of PKCδ (see PKCδ IP in Fig. 4A). Although the tyrosine-phosphorylated form of PKCδ has been previously localized to the membrane fraction(5.Denning M.F. Dlugosz A.A. Howett M.K. Yuspa S.H. J. Biol. Chem. 1993; 268: 26079-26081Abstract Full Text PDF PubMed Google Scholar, 29.Li W. Yu J.C. Michieli P. Beeler J.F. Ellmore N. Heidaran M.A. Pierce J.H. Mol. Cell. Biol. 1994; 14: 6727-6735Crossref PubMed Google Scholar), the tyrosine-phosphorylated PKCδ in the membrane reaction mixture is not endogenous PKCδ formed in vivo because the amount of tyrosine-phosphorylated PKCδ is very low in normal keratinocytes (see Fig. 1, Fig. 3, and Fig. 5).Figure 4:Tyrosine phosphorylation of PKCδ by Src family kinases. In A, recombinant PKCδ from baculovirus-infected Sf-9 insect cells was incubated alone or with purified EGFR, c-Src, c-Fyn, or a membrane fraction from untreated normal keratinocytes in tyrosine kinase assay buffer as indicated. Total reaction mixtures and PKCδ immunoprecipitated from the reactions were analyzed for phosphotyrosine by immunoblotting with anti-phosphotyrosine antibody. In B, 10 μg of membrane protein from untreated keratinocytes were incubated with the indicated clearing antibody followed by protein A-Sepharose, and the cleared lysate was added to recombinant PKCδ for the tyrosine kinase assay. The reaction mixtures were immunoprecipitated for phosph